Two improved extrapolated gradient algorithms for pseudo-monotone variational inequalities - Tang, Haoran; Gong, Weiqiang (AIMS mathematics, 2025)
In this paper, the approximation problem for pseudo-monotonic variational inequalities is studied. With the help of the reciprocal form of parameters and the golden section ratio, two kinds of algorithms are introduced, and their strong convergence is proved under certain appropriate conditions.